Review of the efficacy and safety of cryoablation for the treatment of small renal masses - Kapoor, Anil; Touma, Naji J.; El Dib, Regina (Canadian Urological Association Journal, 2013)
Purpose: Small renal masses are increasingly being discovered incidentally on imaging for another reason. The standard of care of these masses involves excision by open or laparoscopic techniques. Recently, ablative techniques, such as radiofrequency ablation (RFA) and cryoablation, have taken a more prominent role in the treatment algorithm of these masses. We evaluate the effectiveness and safety of cryoablation to treat renal tumours. Methods: A review of the literature was conducted. There was no language restriction. Studies were obtained from the following sources: the Cochrane Library, PUBMED, EMBASE and LILACS. Results: There was no clinical trial identified in the literature. Thus, we described the results from 23 case series and retrospective studies with a reasonable sample size (number of reported patients in each study ≥30), with a total of 2104 analyzed tumours from 2038 patients. There was wide variability in the outcomes reported, but success rates were generally good. Follow-up was generally short, but some series reported outcomes at 5 years. The most common complications reported were hemorrhage (some of the patients requiring transfusion), perinephric hematoma and urine leaks. Conclusion: Cryoablation presents a feasible treatment for patients with small renal masses. Only short-term data are available and, as such, meaningful conclusions regarding long-term cancer control cannot be made. More rigorous studies are needed.